Self Disclosure Pengguna Tinder Dalam Sexting Pada Kencan Digital Selama Pandemi Di Kota Denpasar - Ruditya, Kadek Agus; Joni, I Dewa Ayu Sugiarica; Pradipta, Ade Devia; Damasemil, Calvin (E-Jurnal Medium, 2022)
Online dating apps have changed the way people find dates, from face-to-face to online encounters. One of the online dating applications is Tinder. Tinder users engage in online interactions such as revealing themselves and sharing personal information as a part of the relationship development process, be it face-to-face or virtual relationships. Self-disclosure in an online occurs when a person discloses his/her personal information via the internet to another person. This study aims to explain the self-disclosure of Tinder users in sexting on digital dating during the pandemic in Denpasar City. This research is a qualitative research using New Media and CMC theory. The results of this study found that the informants in this study had the same initial goal of using Tinder, using Tinder to find new relationships as well as being a medium of entertainment during a severe pandemic situation in early 2020. During the self-disclosure process, three informants only share general information such as the area of ??origin, occupation and also busyness. All three also strictly avoid sharing too personal information related to their privacy. The informants acknowledged that sexting activities carried out with matches did not fully help fulfill their sexual satisfaction, but it is undeniable that in the midst of a pandemic, this sexting became an alternative for the three informants in fulfilling their online sexual satisfaction, because according to the three informants, sexting can be foreplay or a way to increase their desire and lust.   Keywords : Self disclosure , Tinder, sexting